Can you please help me solve this problem: Find all real functions that satisfy the functional equation $f(xy+x)+f(y)=f(xy+y)+f(x)$? I should solve it using the following theorem:

Let $f\colon R\rightarrow R$ satisfy the Hosszu functional equation $$f(x+y-xy)+f(xy)=f(x)+f(y)$$

for all $x,y \in R$. Then there exists an additive function $A\colon R \rightarrow R$ and a constant $a\in R$ such that $$f(x)=A(x)+a.$$

Any advice would be helpful. I tried putting $x=y=1$ but didn't know what to do next.

  • $\begingroup$ Is $f$ continuous or not? $\endgroup$ – Sharky Kesa May 31 '18 at 13:03
  • $\begingroup$ Not explicitly stated. I also have a couple of problems where it says "Find all continuous functions..." so I think it doesn't have to be. $\endgroup$ – nix_nicis May 31 '18 at 13:13
  • $\begingroup$ A solution is given on page 211: books.google.co.uk/… $\endgroup$ – Winther Jun 1 '18 at 11:53
  • $\begingroup$ Thank you! But it still doesn't occur to me how should I use the proof of the theorem to solve it since this is the first time I'm seeing functional equations in two variables. If it's trivial, don't bother; hope I'm going to get it soon. $\endgroup$ – nix_nicis Jun 1 '18 at 12:52

Note that this functional equation requires continuity to have well-defined solutions. Otherwise, any function that satisfies Cauchy's functional equation also satisfies this, and there may be other pathological functions (I haven't found any yet though).

Now, if we assume $f$ is continuous, we have:

Firstly, we note that if $f(x)$ satisfies the equation, so does $f(x)+C$ for any real constant $C$. Thus, assume $f(0)=0$.

Let $P(x,y)$ denote the assertion $f(xy+x)+f(y)=f(xy+y)+f(x)$.

Lemma 1: $f(x) = x f(1)$ $\forall x \geq 0$


Let $x > y > 0$. Consider the sequence $y_0 = y$, $y_{n+1} = \frac{x^2+xy_n+y_n}{x+y_n+1}$. We note that $y_n$ is an increasing sequence with a limit of $x$.

$$P \left ( \frac{x-y_n}{x+y_n+1}, x+y_n \right ) \implies f(x-y_n)+f(x+y_n)=f(x-y_{n+1})+f(x+y_{n+1})$$

From this, we get $f(x-y_n)+f(x+y_n) = f(x-y)+f(x+y)$. Sending $n \to \infty$ and using continuity yields $f(x-y)+f(x+y)=f(2x) \; \forall x>y>0$. Thus, we get $f(x)+f(y)=f(x+y) \; \forall x, y >0, x\neq y$. Using continuity, we get $f(x)+f(y)=f(x+y) \; \forall x, y \geq 0$,s o $f(x)=xf(1)$. $_\square$

Lemma 2: $f(-x)=-f(x) \; \forall x$

Consider the sequence $x_0 = x$, $x_{n+1}=\dfrac{x_n}{x_n+1}$. Note that $x_n$ is a decreasing sequence tending to $0$.

$$P(x_n, -x_{n+1}) \implies f(-x_{n+1}) + f(x_{n+1}) = f(-x_n) + f(-x_n)$$. Thus, $f(-x_n) + f(x_n) = f(-x) + f(x)$. Sending $n \to \infty$ and using continuity yields $f(x)+f(-x) = f(0)+f(0)=0$. Thus, $f(-x)=-f(x)$. $_\square$.

Thus, we have $f(x)=ax$ for some constant $ \in \mathbb{R}$. Accounting in the original assumption, we have $f(x)=ax+b$, where $a,b \in \mathbb{R}$, for $f$ continuous.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.